Automation in cargo loading/unloading processes: Do unmanned loading technologies bring benefits when both purchase and operational cost are considered? - Valentin Carlan; David Ceulemans; Edwin Van Hassel; Stijn Derammelaere; Thierry Vanelslander (Journal of Shipping and Trade (JST), 2023)
The use of technologies that automate handling goods and loading units in warehouses and depots is not new. Yet, the purchase process of these technologies issues troubles and the estimation of the economic advantages brought by one or another technology to the entire chain of operations in logistics are not always known. Faults or not documented decisions put pressure on managers and prices for services. They can cause a drop in the competitiveness of warehouse operators, particularly in uncertain conditions. Academia documented the cost of warehouse storage well. Yet, little research has looked into the economic justification of implementing automatic systems for loading or unloading activities and the impact on complementary operations. For this reason, a model is needed to calculate the cost of operations when different technical equipment is used. This research further investigates the cost categories that must be considered when purchasing automated loading/unloading technologies. The model includes the purchase and operational loading costs that new technologies generate and the cost of adjacent operations to loading activity. The case study uses forklifts as the reference scenario and provides an overview of the return on investment and a break-even period when other technologies are in use. The calculation model shows that increasing cargo volume leads to a better RoI. The same observation is also made regarding the rise in labour costs. For the latter, using human operators to handle pallets on a one-by-one basis generates an exponential increase in operational cost due to delays and faults. On the other side, the cost of implementing automated loading/unloading technologies and the consideration of technology risk determine the low economic advantages. An in-depth cost and benefit analysis shows in which situation a technology generates greater benefits. Further results of this paper show that better use of trucks' loading capacity can positively impact the financial performance of automated loading technologies, as a higher volume of cargo is moved (at once) without human intervention.
Keywords: 650; Automation; Cost and benefits; Loading and unloading technologies; Return on investment